Purchasing Process Automation and its impact on international buyer supplie relationships... A case study of Wärtsilä - Arslan, Ahmad (My University, 2007)
Over the past decades purchasing has evolved from an administrative function to a key strategic activity in organization. Automation of the purchasing process in companies by means of electronic solutions is becoming need of time due to need for efficiency and effectiveness in competitive business environment. The main objective of this study was to analyze the automation of purchasing process in organization and how it affects international buyer supplier relationships. The study was made as single case study to find out answers to scientific research questions. Theoretical framework was based on previous researches and literature regarding purchasing process, different automation tools available like EDI and e-procurement and international buyer supplier relationships. It also tries to examine that how culture affects international buyer supplier relationship and automation process. A qualitative method has been employed, in order to get a more precise and deep knowledge of the subject. The author has conducted interviews with concerned Wärtsilä manager in the engine division. The study found that there are several areas in the purchasing process that still can be more efficient by automating it. Moreover, it is possible to conclude that an automation of a purchasing process will have an effect on the international buyer-supplier relationship. The suppliers also need to be taken into confidence before trying to implement any electronic solutions. As automation requires investment, so the companies should thoroughly study on what electronic solution is most suitable keeping in view consideration to what type of product and international supplier one is dealing with.
Keywords: Purchasing Process; e-procurement; automation; international buyer supplier relationships.; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|